2014
DOI: 10.1371/journal.pone.0101896
|View full text |Cite
|
Sign up to set email alerts
|

Synovium Fragment-Derived Cells Exhibit Characteristics Similar to Those of Dissociated Multipotent Cells in Synovial Fluid of the Temporomandibular Joint

Abstract: Multipotent mesenchymal stem cells (MSCs) found in the synovial fluid (SFMSCs) of the tempromandibular joint (TMJ) remain poorly understood. During TMJ arthrocentesis, we discovered that synovial fluid collected from some patients with TMJ disorders contained not only SFMSCs but also synovium fragments (SFs). In this study, we attempted to characterize both the SFMSCs and SF-derived cells (SFCs) in order to further understand the role of MSCs in the synovial fluid of the TMJ. The SFs were membranous and transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 38 publications
3
42
0
1
Order By: Relevance
“…Expression of CD34 was not found in any of the analyses (0.02 % SF-H, 0.09 % SF-OCD, 0.11 % SF-OA, 0.02 % SM-H, 0.10 % SM-OCD, and 0.04 % SM-OA). These results are similar to findings from several previously conducted studies on human cells in which MSCs from SF and SM have exhibited either low or no expression of CD34 [3639]. Only one study has been published that used equine MSCs from SF, and it indicated that there was no expression of CD34 in these cells [12].…”
Section: Discussionsupporting
confidence: 88%
“…Expression of CD34 was not found in any of the analyses (0.02 % SF-H, 0.09 % SF-OCD, 0.11 % SF-OA, 0.02 % SM-H, 0.10 % SM-OCD, and 0.04 % SM-OA). These results are similar to findings from several previously conducted studies on human cells in which MSCs from SF and SM have exhibited either low or no expression of CD34 [3639]. Only one study has been published that used equine MSCs from SF, and it indicated that there was no expression of CD34 in these cells [12].…”
Section: Discussionsupporting
confidence: 88%
“…The second limitation is that the tissue origin of hSF-MSCs has remained unclear until now. According to a study from The International Society for Cellular Therapy (ISCT), a criterion was proposed to define human MSCs, describing them to stain positive for CD105, CD73, and CD90 and stain negative for CD45, CD34, CD14 or CD11b, CD79a or CD19, and HLA-DR (Dominici et al, 2006;Sun et al, 2014). The third limitation to this study is that while we have analyzed several cell surface markers, we have not analyzed all of them here.…”
Section: Discussionmentioning
confidence: 99%
“…The local delivery of mesenchymal stem cells (MSCs) within TMJ has proved to have beneficial effects on TMJ degenerative diseases [79]. Furthermore, another strategy would be stimulating the resident mesenchymal stem cells present in the synovial layer [102] and synovial fluid of TMJ [103]. MSCs are able to secrete bioactive molecules, such as growth factors, cytokines, and chemokines, which exert their biological role under injury conditions [104].…”
Section: Scaffoldsmentioning
confidence: 99%